Correlation of serum creatinine kinase muscle-brain fraction and lactate dehydrogenase with severity of hypoxic ischemic encephalopathy in perinatal asphyxia in term neonates - K., Masaraddi Sanjay; P. M., Ahamed Roshan; P., Nedunchezhian; C., Sulekha (International Journal of Contemporary Pediatrics, 2018)
Background: Birth asphyxia in neonates significantly contributes to their mortality and morbidity, as it leads to hypoxic ischemic encephalopathy (HIE) and multi organ dysfunction. The present study was conducted with an objective to ascertain whether serum levels of creatinine kinase muscle-brain fraction (CK-MB) and lactate dehydrogenase (LDH) can distinguish an asphyxiated from a non-asphyxiated term neonate and correlation of these enzymes cut-off levels with severity of HIE in asphyxiated term neonates. Methods: This prospective study was conducted at Sree Mookambika Institute of Medical Sciences, Kulasekharam, Kanyakumari from September 2012 to December 2013. The study included 50 cases (asphyxiated neonates) and 50 controls (non-asphyxiated neonates) after fulfilling the requirements of inclusion criteria. Their blood samples were collected at 8±2 hours and 72±2 hours of age for estimation of CK-MB and LDH respectively and sent for analysis. The values were compared between cases and controls by using descriptive statistics. Results: The mean CK-MB level at 8±2 hours and mean LDH level at 72±2 hours were significantly higher in cases compared to controls with p<0.001. Among the 50 neonates in case group, 19 (38%) had clinical evidence of HIE. Of them 3 (6%) had mild HIE, 12 (24%) had moderate HIE and 4 (8%) had severe HIE during the course in NICU. The correlation of Apgar scores of 0-3 and 4-6 at 1 minute and 5 minutes with the severity of HIE and the correlation of cut-off CK-MB level of 92.6 U/L and cut-off LDH level of 580 U/L with the severity of HIE were not significant (p>0.05). Conclusions: We conclude that estimating the levels CK-MB at 8 hours of life and LDH at 72 hours of life can help to distinguish an asphyxiated from a non-asphyxiated term neonate with reasonable degree of accuracy but the enzyme cut-off levels do not correlate with severity of HIE in asphyxiated term neonates.